(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Kikar wood and ash species grown in Quetta have been studied for their anatomical properties in order to find out wood quality improvement before their utilization for making various products. Permanent slides of cross, radial and tangential sections were prepared, observed under the microscope and data were collected for the frequency and dimensional measurement of different wood elements/structures in each wood species. On the basis of results it was observed that Kikar wood may be better or medium in strength due to longer, thick-walled or narrow lumen fibers. In this study kikar locally grown wood species have been evaluated for their basic anatomical properties, in order to find out measures for wood quality improvement before their utilization for making various products. Further, the proposed study will introduce integrated uses of the studied kikar wood species extend the base of raw material for wood based industries result indicate that ash wood grown in Quetta are good in strength and hardness. The frequency of wood rays both in cross and tangential sections was found greater in Ash wood grown in Quetta, Balochistan that indicates the wood is comparatively lower in resistance against decaying agents. The length of fibers, their diameter and wall thickness were found nearly analogous in both wood samples which represents their similarity in strength and hardness.